Response of N (ZA), Si (Silicate) Fertilizers to the Intensity of Sugarcane Streak Mosaic Virus (SCSMV) Attacks on Sugarcane (Saccharum officinarum L.) - Dhoan Bernadi (Contributions of Central Research Institute for Agriculture, 2021)
This study was conducted to determine the effectiveness of using N, Si fertilizers at certain doses to prevent further attacks caused by SCSMV. The results showed that each increase in the dose of N fertilizer on sugarcane plants will accelerate the incubation period with a regression value of 1.038% and affect the increase in intensity SCSMV attack of 3,063%. At each increase in fertilization the dose of Si can inhibit the incubation period of SCSMV and can decrease SCSMV attack intensity of 7.018%. There was no significant difference in the growth of sugarcane shoots in the F test. The use of N dose of fertilization would affect the growth process, such as plant height in increasing the N dose would affect the highest plant height increase in the 8 kw/Ha treatment. In the Si fertilization treatment there was a significant difference that each increase in dose would increase the process of plant height growth. Sugarcane (Saccharum officinarium L.) is one of the plants belonging to the grass species (Gramineae). This plant is used as raw material for sugar. Low sugar production affects the fulfillment of national sugar needs. Many things can affect the decline in sugar production, including the explosion of pests and sugarcane plant pathogens. One of the main pathogens is Sugarcane streak mosaic virus (SCSMV) which in recent years has attacked sugarcane plantations in Indonesia. The role of many nutrients needed by plants. The use of appropriate N nutrients can increase yields, and the application of Si elements can protect plants from OPT attacks.